Sintaxonomy of Pruno-Rubion ulmifolii (Prunetalla) in Spain - Arnáiz, Carlos; Loidi, Javier (Lazaroa, 2014)
The communities of the aliance Pruno-Rubion ulmifolii O. Bolós 1954 in Spain are analyzed through the inventaries published, presenting a synthetic table of it.